Efektivitas Pemanfaatan Cerita Anak Interaktif untuk Meningkatkan Kemampuan Literasi Membaca Siswa SD Kelas Rendah - Sonya Sonya; Ibnu Muthi (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
Reading literacy skills are an important foundation in the learning process of lower grade elementary school students. Unfortunately, many students have difficulty in understanding reading and have low reading interest. This study aims to examine the effectiveness of the use of interactive children's stories in improving the reading literacy skills of lower grade elementary school students. The method used was a quasi-experimental method with a pretest-posttest non-equivalent control group design. The subjects of the study consisted of two classes: an experimental class that used interactive children's story media, and a control class that used conventional methods. The results showed that students who learned with interactive children's stories experienced significant improvements in three main aspects of literacy, namely word recognition, reading comprehension, and reading interest. This media provides a fun and contextual reading experience through a combination of audio, visuals, and interactivity. In addition, students are more enthusiastic and active during the learning process. Thus, interactive children's stories have proven effective as an alternative to innovative literacy learning that is in accordance with technological developments. It is recommended that teachers integrate this media into learning and schools support the development of infrastructure that supports the use of digital media in the classroom.